The Main Trends for Arranging Project Activities in Practice of the Modern Elementary School - Larskikh, Zinaida Petrovna; Almazova, Irina Gennadievna; Chislova, Svetlana Nikolaevna; Chibuhashvili, Valentine Alexandrovna (International Review of Management and Marketing, 2016)
The quality of training schoolchildren is the guarantee for successful implementation of educational mission in elementary school. The quality criteria include the development of creative abilities and skills of self-cognition, self-education, and self-fulfillment. Among the means of ensuring the subjective position of a primary school aged child, which create a favorable environment for the formation of readiness for self-development, the scientists distinguish design technologies that require active involvement and learner's immersion into the process of self-education. It is necessary to identify more clearly and specifically both external and internal factors that contribute to the formation of readiness in schoolchildren of elementary grades to implement project activities, to determine optimal pedagogical conditions of implementation thereof. The priority among these project activities belongs to the use of design technologies in educational process that contribute to the development of reflective skills, independent work skills, increase of creativity, activation of cognitive interest in the partnership subject-subject interaction of junior schoolchildren and teachers. This article defines the main directions of project activities in the practice of a modern elementary school. It selects and analyzes the targets of project activities of junior schoolchildren. The authors focus on three areas of implementing project activities in secondary schools: curricular, educational, extra-curricular activities, as well as in the process of integration of these forms. The content of the article includes characteristics of educational work on local history and civic education of schoolchildren by means of project activities. As an example arrangement of project activities for junior schoolchildren in the subjects "Mathematics" and "Russian language" is considered. The article analyzes the content of the "School of Russia" program and identifies its opportunities for arranging project activities on mathematics. The authors revealed possibilities of arranging project activities for elementary school during the extracurricular hours to produce a linguistic identity of a child. Keywords: project method, project activities, elementary school, schoolchildren, extracurricular activities, learning process. JEL Classifications: I210, I280